Earnings Management in Small Listed Firms in Malaysia Using Quantile Regression - Shamsul Nahar Abdullah (International Journal of Business and Society, 2022)
This study examines the role of board independence and audit committee expertise in accounting on earnings management in small listed firms in Malaysia, which have been neglected in corporate governance research. Due to their small size, the listing requirements imposed on them by Bursa Malaysia are less stringent. Hence, these firms are predicted to have a higher tendency to manage earnings compared to large listed firms. All firms listed on the Bursa Malaysia ACE Market during the financial years 2012 to 2014 inclusive were selected. The data were analysed using quantile regression to enable the determination of the effects of the corporate governance variables across the quantiles in the conditional distribution of discretionary accruals. The results show that small listed firms have a very high propensity for accrual management compared to large listed firms. The study also reveals that board independence is not associated with either the incidence of accrual management or the direction of discretionary accruals. It also shows that audit committee expertise can mitigate the propensity for discretionary accruals and if discretionary accruals are present, the objective was to reduce the firm’s earnings. However, this evidence only holds in firms where the utilization of discretionary accruals is pervasive.